2017
DOI: 10.17844/jphpi.v19i3.15104
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chitosan as Antibacterial for Pangasius Fillet at Low Temperature Storage

Abstract: Cara sitasi: Damayanti W, Rochima E, Hasan Zahidah. 2016. Aplikasi kitosan sebagai antibakteri pada filet patin selama penyimpanan suhu rendah. Jurnal Pengolahan Hasil Perikanan Indonesia 19(3): 321-328. AbstrakPenelitian ini bertujuan untuk mendapatkan konsentrasi kitosan yang optimal sebagai bahan antibakteri dengan masa simpan filet patin paling lama pada penyimpanan suhu rendah (5-10 o C). Metode yang digunakan yaitu metode eksperimental dengan rancangan acak lengkap, dengan empat perlakuan dan tiga ulanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
6
1
4
Order By: Relevance
“…The increasing of TVC in the red snapper coated with chitosan was higher compared to control (1% acetic acid). This finding was different with study done in other study [9] which applied chitosan on Pangasius pangasius fillet under chilling condition. They found that the total plate count of the pangasius fillets with the addition of chitosan were not exceeded log 5 CFU/g up until 9 days for 1% chitosan and 11 days for 2 and 3% chitosan.…”
Section: ) Microbiological Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…The increasing of TVC in the red snapper coated with chitosan was higher compared to control (1% acetic acid). This finding was different with study done in other study [9] which applied chitosan on Pangasius pangasius fillet under chilling condition. They found that the total plate count of the pangasius fillets with the addition of chitosan were not exceeded log 5 CFU/g up until 9 days for 1% chitosan and 11 days for 2 and 3% chitosan.…”
Section: ) Microbiological Analysiscontrasting
confidence: 99%
“…The other study showed that application of 1% (w/v) of chitosan on smoked milk fish at room temperature retained the microbiological quality up to seven days [13]. However, based on starting point of the application of chitosan was log 4 CFU/g, both result this study and Damayanti [9] were able to maintain the microbiological quality up until three days. This study indicated that the initial microbiological quality of the fish will affect the storage of the fish.…”
Section: ) Microbiological Analysismentioning
confidence: 62%
“…Selain itu juga pemanfaatan kitosan juga berguna baik untuk industri tekstil, pengobatan, makanan, dan degradasi limbah logam berat (Pujari & Pandharipande., 2016;Uthairatanakij, et al, 2007). Penelitian Damayanti et al (2016) bahwa kekampuan kitosan dapat memperlama umur simpan fillet ikan patin selama 11 hari. Melihat potensi yang dimiliki oleh kitosan maka peneliti tertarik untuk memanfaatkan potensi kitosan cangkang bekicot yang diaplikasikan pada tahu putih terhadap organoleptik, bobot susut, dan lama simpan.…”
Section: Pendahuluanunclassified
“…Tahu putih kontrol asam asetat dengan nilai simpangan baku 17,64, tahu putih yang diberi aquadest nilai simpangan baku 15,11, tahu putih yang diberi kosentrasi kitosan cangkang bekicot 1% dengan simpangan baku 13,79%, kosentrasi 1,5% simpangan baku 22,22, kosentrasi kitosan 2% simpangan baku 20,47. Perlakuan pada kosentrasi 2% bobot susut lebih kecil sesuai dengan penelitian Damayanti et al (2016).…”
Section: Hasil Dan Pembahasanunclassified
“…Based on the results of the examination, the ruku-ruku leaf stock solution used in the study had a slightly acidic pH value of 6.0, so that this value could affect the pH of Indian mackerel. Naturally, the pH in fish meat will decrease at the beginning of the storage period and then rise until the pH reaches base [36].…”
Section: Acidity (Ph)mentioning
confidence: 99%